Conexões entre o mundo on-line e a vida off-line: otakus e cultura de consumo na era da internet - Cavalcante, João Paulo Braga (2008)
This research aimed to analyze the subjects related to social changes in the contemporary consumption culture due to interaction between social players and new electronic medias according to World Wide Web This interaction comes from the social player’s growing autonomy against the authorized issuer of product and information I’ve founded that consumer networks structured by subcultures have created unauthorized channels of sharing of messages circumventing the law This phenomenon was observed in a consumption subculture known as otaku whose origin is Japanese This term means an enthusiast of Japanese animes mangas cartoon and comics The otakism is a movement intrinsic to culture globalization and it looks at a powerful connection between new digital technologies and post-1980s youth that is more individualistic and more independent of authorized medias The growth of otakism could be observed in Fortaleza a city that hosts every year one of the biggest anime convention in Brazil called Super Amostra Nacional de Animes (SANA) Its numbers of visitors grows years after years The qualitative and quantitative methods of analyze were used in this research including exploratory poll in SANA event non-structured interviews and ethnography in virtual ambients The last one was designed to understand the quality of social relations in the multidirectional new medias where all players are issuers receptors and creators at the same time The research discovered that otaku subculture has been adapting the new digital technologies particularly the Internet for its consumption purposes and expansion of the possibilities of interpersonal relationships